(NpODZEMNYE LXDY eNISEJSKOGO sEWERA (B/s - (NkARPOW(B, (NeGOR gAWRILOWI^s ((NnOWOSIBIRSK (B:s (NnAUKA(B. (NsIB(B. (NOTD(B-(NNIE(B,s, 1986)
(NbIBLIOGR(B.: (NS(B. 123-132s
(Nan sssr(B, (NsIB(B. (NOTD(B-(NNIE(B, (NiN(B-(NT MERZLOTOWEDENIQs
Keywords: (NlED PODZEMNYJs